2010
DOI: 10.1292/jvms.09-0557
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Virulence Genes Related to Adhesions and Toxins in Shiga Toxin-Producing Escherichia coli Strains Isolated from Healthy Cattle and Diarrheal Patients in Japan

Abstract: ABSTRACT. Shiga toxin-producing Escherichia coli (STEC) isolated from Japan were investigated for the distribution of virulence genes. A total of 232 STEC strains including 171 from cattle and 61 from human were examined for the occurrence of genes responsible for bacterial adhesions to intestine, e.g., eae (intimin, E. coli attaching and effacing), saa (STEC autoagglutinating adhesin), iha (irgA homologue adhesin), efa1 (E. coli factor for adherence), lpfA O113 (long polar fimbriae), and ehaA (EHEC autotransp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 39 publications
1
31
0
6
Order By: Relevance
“…In addition, subtilase cytotoxin (SubAB) was discovered in STEC O113:H21 strain 98NK2, which was responsible for an outbreak of HUS (5). SubAB is produced primarily by a variety of non-O157 serotypes of STEC; STEC O157:H7, the most common serogroup implicated in hemorrhagic colitis and HUS, almost never produces SubAB (6)(7)(8)(9). SubAB has an enzymatically active subunit, which is a subtilaselike serine protease, and five receptor recognition domains, which play important roles in binding to the receptor on the target cell surface (5).…”
mentioning
confidence: 99%
“…In addition, subtilase cytotoxin (SubAB) was discovered in STEC O113:H21 strain 98NK2, which was responsible for an outbreak of HUS (5). SubAB is produced primarily by a variety of non-O157 serotypes of STEC; STEC O157:H7, the most common serogroup implicated in hemorrhagic colitis and HUS, almost never produces SubAB (6)(7)(8)(9). SubAB has an enzymatically active subunit, which is a subtilaselike serine protease, and five receptor recognition domains, which play important roles in binding to the receptor on the target cell surface (5).…”
mentioning
confidence: 99%
“…In this study, both O91:H14 strains carried the toxin gene. CDT has been detected in eae-negative EHEC strains isolated from both humans and domestic animals (13,26). In addition, 2 cdt-carrying strains were obtained, and of those, 1 was eaenegative (O112ab:H25) and the other was eae-positive (O111:NM).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, virulence factors associated with disease in calves can be detected in healthy adult cows (6,25,29,30). Based on these studies of E. coli from different healthy animal species from various geographical locations, it appeared that virulence factors were found in healthy animals regardless of geographical origin.…”
Section: Vol 76 2010 Virulence Factor Profiling Of Veterinary E Comentioning
confidence: 99%
“…The PCR-based approach will likely allow for the detection of virulence factors in a population of E. coli. Numerous studies have found that E. coli isolates from healthy animals contain virulence genes; however, the prevalence is typically lower than that in diseased animals (20,21,30). Therefore, the ability to screen populations of E. coli for virulence genes will likely be beneficial when strains containing the source-associated virulence factors are present in the animal population at a relatively low frequency.…”
Section: Vol 76 2010 Virulence Factor Profiling Of Veterinary E Comentioning
confidence: 99%
See 1 more Smart Citation